Premature acute coronary syndrome. (25th November 2020) - Menezes Fernandes, R; Mota, T; Bispo, J.S; Azevedo, P.M; Bento, D; Guedes, J; Carvalho, D; Marques, N; Santos, W; Mimoso, J; Jesus, I
Abstract: Introduction: The prevalence of acute coronary syndrome (ACS) at an early age is rising, resulting in higher morbidity and mortality rates. Purpose: To characterize patients admitted with premature ACS, comparing with those with non-premature ACS. Methods: A retrospective study encompassing patients of a National Registry of ACS was performed. We compared two groups: one composed of men <55 and women <65 years-old; and other with men ≥55 and women ≥65 years-old at the ACS admission. Clinical characteristics, in-hospital evolution and 1-year clinical outcomes were analysed. Primary endpoint was the composite of in-hospital mortality, stroke and re-myocardial infarction (MI). Secondary endpoints were re-MI, stroke, in-hospital and 1-year mortality, 1-year cardiovascular (CV) and non-CV readmissions. Results: A total of 26523 patients were enrolled and 6637 (25%) had premature ACS, with a mean age of 49±7 years-old. It was found a larger prevalence of smoking habits, obesity and dyslipidemia, but not diabetes. ST-segment elevation MI (STEMI) was the main admission diagnosis (51, 2% vs 40, 3%), with more frequent activations of the STEMI network (17, 1% vs 12, 8%) and a consequently shorter time from symptom onset to admission (483 vs 584 min). Coronary angiogram was largely performed in younger patients (91, 4% vs 82, 1%), mainly revealing one-vessel disease (49, 3% vs 34, 3%). They had lower Killip-Kimbal (KK) class (6% vs 18, 1% with KK class >1) and mostly preserved left ventricular ejection fraction (LVEF) (67, 3% vs 58, 6%). Major bleeding (0, 9% vs 1, 7%), sustained ventricular tachycardia (1, 1% vs 1, 5%) and mechanical complications (0, 2% vs 0, 7%) were uncommon. Composite endpoint was more frequent in non-premature ACS patients (6, 2% vs 1, 9%). Non-premature age, KK class >1, multivessel disease and depressed LVEF were independent predictors of primary endpoint (each with p<0, 001). Younger patients had inferior rates of in-hospital mortality (1% vs 4, 7%), re-MI (0, 5% vs 1%) and stroke (0, 4% vs 0, 7%). One-year mortality (1, 7% vs 9, 1%), and 1-year CV (9, 7% vs 15, 5%) and non-CV readmissions (3, 7% vs 8, 2%) were also lower. All comparative data presented have a statistically significant p-value (p<0, 012). Conclusions: Premature ACS affects 25% of the ACS population, mostly presenting with STEMI, but generally associated with better clinical evolution. Nevertheless, primary prevention is essential to correct modifiable CV risk factors and reduce coronary events in these patients. Funding Acknowledgement: Type of funding source: None